Yeast diversity in tropical fruits from Costa Rica - Rojas-Jiménez, Keilor (2025)
Introduction: The yeasts consumed by the population in foods such as tropical fruits remain relatively unknown, despite being an important component of the human microbiota and having multiple biotechnological applications. Methods: In this work we isolated and characterized the diversity of yeasts in fruits regularly ingested in Costa Rica, using culture-dependent methods, morphological characterization, and ITS marker sequencing. Results: We isolated 118 yeasts from the 26 species of tropical fruits sampled, grouped into 7 families, 11 genera, and 19 species. Hanseniaspora pseudoguilliermondii, Pichia kluyveri and Hanseniaspora uvarum were the most abundant species. Notably, some species were present on several fruits, others presented a more specific host range, and some were only isolated after several months of fermentation. Conclusion: Our work evidences the large diversity of yeasts present in tropical fruits, which motivates further study of their ecology, physiology, and potential biotechnological uses. Keywords